PHYSICAL CONFORMATION AND ULTRASONOGRAPHIC APPROACHES FOR BREEDING SOUNDNESS EVALUATION OF HIGH AND LOW LIBIDO CROSSBRED BULLS - KUMAR, A; SINGH, K; HONPARKHE, M; KAUR, S; GHUMAN, S P S; BRAR, P S (The Indian Journal of Animal Reproduction, 2016)
Physical conformation, scrotal circumference, testicular volume, rump fat thickness, testicular echogenecity and accessory sex glands diameter in relation to libido (poor or high) in crossbred breeding bulls (n=22) was evaluated. Internal pelvic area (1121.60±42.19 vs 959.14±75.20 cm2) and testicular volume (454.30±21.51 cm3 vs 393.65±27.06 cm3 ) were higher (p<0.05) in high libido bulls. Rump fat thickness was lower (3.90±0.47 vs 6.03±1.17 mm) in high libido bulls (p<0.05). The scrotal circumference, hock joint angulation, diameter of prostate and diameter of seminal vesicles were similar in both groups (p>0.05). Thus, internal pelvic area, testicular volume and ultrasound based rump fat thickness are associated with problem of poor libido in breeding crossbred bulls.